Efficacy and safety of Sri Lankan traditional medicine regimen for knee osteoarthritis: study protocol for an open-label, active comparator, randomized controlled trial - De Silva, H.; Perera, P.K.; Jayasinghe, S.; Weliange, S.D.S. (BioMed Central Ltd - Springer Nature, 2022)
Background: Knee osteoarthritis (KOA) is the most common form of arthritis, causing disability and impaired quality of life especially in the elderly. Sri Lankan traditional medicine (STM) is widely used to treat OA, but no clinical trial evaluated on STM regimens for KOA to discuss their safety and efficacy in the treatment. The aim of this study is to compare the efficacy and safety of STM regimen for KOA in comparison to recommended conventional pain management therapy over a period of 8 weeks on relieving the condition. Study design: This is a clinical trial following a protocol-driven open-labeled randomized controlled study enrolling patients with KOA that will be conducted as a single-center trial in the National Ayurveda Teaching Hospital, Sri Lanka. Rasnadvigunabhagasaya herbal decoction (RDBD) and an herbal pill Yoaraja Guggulu were selected as the rescue medication for treating joint disorders. The two Ayurvedic dosage forms will be tested against the non-steroidal anti-inflammatory drugs tab paracetamol and tab ibuprofen as the rescue medication for their safety and efficacy. As test products for external application, oil with an herbal fomentation—Kumburuetaperumkayam Pottani (KAP)—and paste—Sandivadam Lepaya (SVL)—were selected. External applications will be tested against the diclofenac sodium gel and hot water fomentation. KOA patients will be allocated randomly into two arms, and the medications will be given orally for 60 days and externally for 30 days. The primary endpoint is the change in the score on the WOMAC after 08 weeks. WOMAC and KOOS will be recorded and compared between the two arms prior to visiting 1, at the end of 15 days and end of 30 days, and end of the 45 days and end of the second month and 3 months of follow-up. KOOS and WOMAC subscales, a pain disability index, a visual analog scale for pain and sleep quality, and a quality-oflife index are used as secondary outcome measurements. Discussion: This clinical trial will be able to provide evidence-based scientific data on Sri Lankan traditional medicine regimens in the management of KOA. This trial is expected to develop capacity to scientifically evaluate various STM that are claimed to have efficacy in treatment of various disease conditions.
Keywords: knee osteoarthritis; Sri Lankan traditional medicine